The ecdysone-induced bZIP transcription factor MafB establishes a positive feedback loop to enhance vitellogenesis and reproduction in the Aedes aegypti mosquito - Jia-Lin Wang; Zi-Qian Zhong; Ya-Zhou He; Jun-Hua Tian; Yu-Feng Wang; Alexander S. Raikhel (Proceedings of the National Academy of Sciences, 2025)
Female mosquitoes require a vertebrate blood meal to activate reproduction, transmitting numerous devastating human diseases. Vitellogenesis is a central event of female reproduction that involves the massive production of vitellogenin (Vg) in the fat body and the maturation of ovaries. This process is controlled by the steroid hormone 20-hydroxyecdysone (20E); however, its molecular regulatory basis remains not completely understood. We found that the expression of Aedes aegypti muscle aponeurosis fibromatosis B ( AaMafB ), coding for a basic leucine zipper (bZIP) transcription factor, was significantly up-regulated after a blood meal. The 20E-bound ecdysone receptor–ultraspiracle heterodimer directly targeted the ecdysone response element in the promoter of AaMafB , activating its transcription. Coimmunoprecipitation assays illustrated the interaction between Aa MafB and Cap “n” collar C ( Aa CncC), another bZIP transcription factor. RNA interference–mediated depletion of Aa MafB or Aa CncC led to impaired ovarian growth, decreased expression of AaVg and Halloween genes, and reduced 20E levels. The Aa MafB– Aa CncC heterodimer directly activated the transcription of AaVg and AaShade by targeting the antioxidant response element in their promoters. Together, our results indicate that AaMafB functions as an early 20E response gene, the product of which heterodimerizes with Aa CncC to maintain high 20E levels and facilitates activation of AaVg in mosquitoes after a blood meal.